(untitled) (Swiss Medical Weekly, 2021)
OBJECTIVE The Swiss Diabetes Registry (SwissDiab) is a multicentre, longitudinal, observational study of outpatients with diabetes receiving treatment at tertiary care centres. The aim of this study was to evaluate the representativeness of the participants at the study centre in the Division of Endocrinology and Diabetes at the Cantonal Hospital of St Gallen by comparing diabetes-related characteristics of participating and nonparticipating patients. METHODS The study included 493 SwissDiab participants enrolled between 1 January 2010 and 31 December 2016 and 640 nonparticipating patients treated at the centre during the same time period. For participants and nonparticipating patients, demographic characteristics, clinical findings, blood chemistry and medication were retrieved from the SwissDiab baseline visit and the medical record ±6 months from the first available outpatient visit to the clinic for diabetes-related care within the study period. Nonparticipating patients were further divided into three subgroups: (i) excluded from SwissDiab, or having received (ii) ≥6 months or (iii) <6 months of prior diabetes treatment at the centre. Differences in diabetes-related clinical characteristics were determined using simple bivariate (nonparametric) statistical analyses stratified by diabetes mellitus type 1 and type 2. RESULTS Compared with nonparticipants, participants smoked less (diabetes mellitus type 1: 24% vs 45%; diabetes mellitus type 2: 21% vs 29%), had higher educational attainment (diabetes mellitus type 1: 39% vs 21%; and diabetes mellitus type 2: 25% vs 18%) and lower glycated haemoglobin levels (diabetes mellitus type 1: 7.2% vs 7.8%; diabetes mellitus type 2: 7.2% vs 8.1%). In diabetes mellitus type 2, the proportion of females (30% vs 38%) and a migration background (36% vs 49%) were lower among participants. (All p-values <0.05.) In a stratified analysis SwissDiab participants had slightly better controlled diabetes than nonparticipating patients with ≥6 months of prior treatment, whereas the diabetes of patients recently referred to the clinic (with <6 months of prior treatment) and patients excluded from participation in SwissDiab were less well controlled. CONCLUSION The observed differences in clinical characteristics between study participants and nonparticipating patients indicate that SwissDiab is likely to overestimate the state of diabetes care and management. The results highlight the need to improve recruitment of females and patients with a migration background in diabetes mellitus type 2. Clinical trial registration number NCT01179815